2023
DOI: 10.1007/s40368-023-00803-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of dental hypersensitivity and anxiety in children with molar-incisor hypomineralisation (MIH)

Abstract: AimThe objective of this study was to investigate whether dental hypersensitivity and dental fear were linked to the presence and severity of MIH. Methods For this cross-sectional study, 1830 students between the ages of 6 and 12 years were recruited from four randomly selected schools. The Children's Fear Survey Schedule-Dental Subscale questionnaire was used to assess dental anxiety and fear. The children's self-reported dental hypersensitivity resulting from MIH was evaluated using the Wong-Baker Facial Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Examining the effect of MIH on DFA is difficult as it is difficult to separate the impact of treatment, particularly in severely affected groups, as one of the most complex and multi-faceted contributions to DFA. More recently, authors reported no evidence of an association between MIH and DFA, confirming the results of Jälevik and Klingberg's landmark study and challenging pervasive clinical dogma [39][40][41][42].…”
Section: Dental Fear and Anxietysupporting
confidence: 53%
“…Examining the effect of MIH on DFA is difficult as it is difficult to separate the impact of treatment, particularly in severely affected groups, as one of the most complex and multi-faceted contributions to DFA. More recently, authors reported no evidence of an association between MIH and DFA, confirming the results of Jälevik and Klingberg's landmark study and challenging pervasive clinical dogma [39][40][41][42].…”
Section: Dental Fear and Anxietysupporting
confidence: 53%
“…All studies that investigated the management of hypersensitivity revealed a reduction after therapy, according to a recent systematic review. However, none of these tactics can be entirely advised due of the moderate-to-high bias risk of the research, short follow-up periods, and small sample sizes [5,23,29].…”
Section: Hypersensitivity Remineralization and Pain Management In Mihmentioning
confidence: 99%
“…The pulp is not adequately protected from external stimuli as hypomineralized enamel is a poor insulator, and the tooth becomes susceptible to hot and cold conditions as a result. Chronic pulp stress causes an inflammatory reaction inside the pulp and pH changes at the periapical tissue level, resulting in hypersensitive pulp nerve tissue that activates with less stimulation than is typically required [29]. Multiple solutions have been proposed in the literature to address this problem.…”
Section: Hypersensitivity Remineralization and Pain Management In Mihmentioning
confidence: 99%
See 1 more Smart Citation
“…MIH is putatively caused by multiple etiological factors [1,2]. MIH is a signi cant concern in modern Pediatric Dentistry due to its high prevalence, impact on the quality of life of affected children and challenges in treatment, particularly in severe cases with dental hypersensitivity, post-eruptive enamel breakdown and/or atypical caries lesions [3,4] The evaluation of mastication di culties and food intake problems in children with MIH have been conducted in a few studies. Ebel et al used speci c questions related to dietary/functional domains from the CPQ 8-10 questionnaire and found that children with severe MIH experienced greater di culty with cold and hard foods [5].…”
Section: Introductionmentioning
confidence: 99%